Cemento-ossifying fibroma - Chandramani More; Krushna Thakkar; Mukesh Asrani (Wolters Kluwer Medknow Publications, 2011)
Cemento-ossifying fibromas (COFs) are benign lesions affecting the jaws and other craniofacial bones. They commonly affect adult females between the third and fourth decade of life, predominantly occurring in the premolar/molar region of the mandible. Most of the lesions typically show slow and often expansile growth, centrally within the jaw and characteristically behave in a benign form, but occasionally they may present as an aggressive gigantiform lesion. Radiographically, they appear as well-defined unilocular or multilocular intraosseous masses. The lesion is invariably encapsulated and of mixed radiolucent densities. The tumor may grow quite extensively; thus, the term "aggressive" is sometimes applied. Surgical resection is the treatment of choice. They are insensitive to radiotherapy and recurrences are uncommon. Clinical, radiographic and histopathologic features of COF and other fibro-osseous lesions are overlapping and may cause confusion in classification, diagnosis and treatment.